2017
DOI: 10.1016/j.yjmcc.2016.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac inflammation in genetic dilated cardiomyopathy caused by MYBPC3 mutation

Abstract: Cardiomyopathies are a leading cause of heart failure and are often caused by mutations in sarcomeric genes, resulting in contractile dysfunction and cellular damage. This may stimulate the production of a robust proinflammatory response. To determine whether myocardial inflammation is associated with cardiac dysfunction in dilated cardiomyopathy (DCM) caused by MYBPC3 mutation, we used the well-characterized cMyBP-C(t/t) mouse model of DCM at 3 months of age. Compared to wild type (WT) mice, DCM mice exhibite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 50 publications
0
50
0
Order By: Relevance
“…Preservation of the mitochondrial electron transport chain, which is the main source of reactive oxygen species and oxidative stress when dysfunctional, is one of the pathways improved by α‐cardiac actin as indicated by the data obtained by the transcriptomic approach. Indeed, several studies have previously suggested a relationship between DCM pathogenesis and oxidative stress . Thus, we examined the impact of α‐cardiac actin on the oxidative stress level in the heart by two approaches using DHE to detect superoxide production and DNA breaks in nuclei and carbonylated proteins by DNPH staining (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Preservation of the mitochondrial electron transport chain, which is the main source of reactive oxygen species and oxidative stress when dysfunctional, is one of the pathways improved by α‐cardiac actin as indicated by the data obtained by the transcriptomic approach. Indeed, several studies have previously suggested a relationship between DCM pathogenesis and oxidative stress . Thus, we examined the impact of α‐cardiac actin on the oxidative stress level in the heart by two approaches using DHE to detect superoxide production and DNA breaks in nuclei and carbonylated proteins by DNPH staining (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Protein carbonyl content (PCOs), a general indicator of protein oxidation, was quantified in the kidney by reaction with 2,4-dinitrophenylhydrazine (2,4-DNPH), as previously shown [17]. Total PCOs were determined from the absorbance at 370 nm using a 2,4-DNPH molar absorption coefficient of 0.022 μM -1 cm -1 , and expressed as nmol/mg protein.…”
Section: Methodsmentioning
confidence: 99%
“…The genotype frequently does not equate to phenotype because of environmental epigenetic influences on gene expression. For example, mutations that promote cardiomyocyte damage recruit a pro-inflammatory response promoting remodelling and DCM 147 . Thus, assessment of familial DCM would bene fit from an improved understanding of the influence of environmental and epigenetic factors 148,149 .…”
Section: Diagnosis Screening and Prevention Diagnosismentioning
confidence: 99%